Practical Preimplantation Genetic Diagnosis - Kuliev, Anver (Springer London : Imprint: Springer, 2013)
Although treatment remains the major goal in the control of genetic disease, this is not yet a reality for most inherited conditions. In the absence of radical treatment, preimplantation genetic diagnosis (PGD) offers the answer to the control of these inherited conditions by predicting reproductive outcome. PGD is now entering its third decade as an established procedure for genetic and assisted reproduction practices, with new and exciting developments changing the whole concept of prevention of congenital disorders. The availability of practical experience from tens of thousands of PGD cases makes it necessary to update the current information on its accuracy, reliability and safety.  The Second Edition of this successful book updates the progress in prevention of genetic disorders to demonstrate the important place of PGD in primary preventive measures and its increasing role in providing the whole range of reproduction options to couples at risk. In addition, it provides an extensive review of the most recent developments within the field of PGD including, PGD for expanding indications, such as de novo mutations, cancers, inherited cardiac diseases and combined PGD for single gene disorders, HLA typing and 24 chromosome testing in patients of advance reproductive age. This practical book is vital for all practitioners within the field of fertility, reproductive medicine and medical genetics. It will also be useful for those responsible for planning and organizing PGD services and provides a working manual for the establishment and performance of PGD in the framework of IVF and genetic practices.  .